Sense data and logical relations: Karin Costelloe-Stephen and Russell's critique of Bergson. Issue 4 (3rd July 2020) - Vrahimis, Andreas
ABSTRACT: Though scholarship has explored Karin Costelloe-Stephen's contributions to the history of psychoanalysis, as well as her relations to the Bloomsbury Group, her philosophical work has been almost completely ignored. This paper will examine her debate with Bertrand Russell over his criticism of Bergson. Costelloe-Stephen had employed the terminology of early analytic philosophy in presenting a number of arguments in defence of Bergson's views. Costelloe-Stephen would object, among other things, to Russell's use of an experiment which, as she points out, was first conducted by Carl Stumpf. Russell appeals to Stumpf's experiment in his attempt to prove that sense data are terms in logical relations, a thesis presupposed by the project of logical analysis outlined in Our Knowledge of the External World . A reformulated version of Costelloe-Stephen's argument put forth by this paper shows that Russell's argument fails to provide adequate proof for his thesis. Further modifications of the argument can also address a reconstruction (based on contemporary reports) of Russell's reply to Costelloe-Stephen. In his reply, Russell would use, already in 1914, the term 'analytic philosophy' in contrasting his and Moore's approach to a continental one, exemplified by Bergson and Costelloe-Stephen.